The influence of purification of carp collagen used in a novel composite graft with sandwich construction of the wall on its biological properties and graft patency rates - Mitas, P; Grus, T; Lambert, L; Mlcek, M; Chlup, H; Honsova, E; Dohnalova, M; Suchy, T; Burgetova, A; Lindner, J; Spacek, M (Physiological research, 2019)
We compared graft outcome between two types of a novel composite three-layer carp-collagen-coated vascular graft in low-flow conditions in a sheep model. Collagen in group A underwent more cycles of purification than in group B in order to increase the ratio between collagen and residual fat. The grafts were implanted end-to-side in both carotid arteries in sheep (14 grafts in 7 sheep in group A, 18 grafts in 9 sheep in group B) and artificially stenosed on the right side. The flow in the grafts in group A decreased from 297±118 ml/min to 158±159 ml/min (p=0.041) after placement of the artificial stenosis in group A, and from 330±164ml/min to 97±29 ml/min (p=0.0052) in group B (p=0.27 between the groups). From the five surviving animals in group A, both grafts occluded in one animal 3 and 14 days after implantation. In group B, from the six surviving animals, only one graft on the left side remained patent (p=0.0017). Histology showed degradation of the intimal layer in the center with endothelization from the periphery in group A and formation of thick fibrous intimal layer in group B. We conclude that the ratio between collagen and lipid content in the novel three-layer graft plays a critical role in its patency and structural changes in vivo.
Keywords: protézy - design; Blood Vessel Prosthesis; Sheep; Prosthesis Design; zvířata; Vascular Patency; cévní protézy; průchodnost cév; Collagen; Animals; kolagen; ovce; Carotid Arteries; Carps; kapři; arteriae carotides